Analisis Tingkat Risiko Banjir pada Daerah Aliran Sungai (DAS) Bialo Provinsi Sulawesi Selatan - Aldiansyah, Farhan; Ahmad, Despry Nur Annisa; Asman, Andi Idham (Jurnal Peweka Tadulako, 2025)
Watershed (DAS) can simply be interpreted as one of the containers that has the function of flowing rainwater into the lake or sea. Land use change in the upper reaches of the Bialo watershed which causes cultivation are one of the causes of flooding in the downstream area of the Bialo watershed. The purpose of this study is to analyze the level of hazard, vulnerability, capacity, and risk of flooding in the Bialo River Basin. The data collection method in this study used interviews, documentation, observation, and literature studies. The analytical methods used in this study are quantitative descriptive methods, spatial analysis, and qualitative descriptive. Quantitative descriptive methods are used to analyze hazard, vulnerability, capacity and risk. Spatial analysis that used in the process of modeling the results of calculating the hazard, vulnerability, capacity, and risks. Qualitative descriptive methods are used to interpret the results of spatial analysis. The results of this study is shows that the level of flood risk in the Bialo watershed consisted of 3 classifications, namely low, medium and high. Low Area 3342.39 Ha, Medium 6748.27 Ha and High 807.86 Ha.